KARAKTERISTIK FISIK DAN KIMIA DARI PRODUK BIOINDUSTRI CANGKANG JAMBU METE (Anacardium occidentale) / Physical and Chemical Characteristics of Bioindustry Products of Cashewnuts Shell (Anacardium occidentale) - Andi Saenab; K. G. Wiryawan; Retnani Y.; E. Wina (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
The shell of the cashew nut industry waste has the potential to produce a product that is biofat bioindustry, biochar and biosmoke. The research aims to produce three products bioindustry, observe the physical and chemical characteristics. Eggshell processed into a particle size of 1 cm and 2 mm size, extracted with hexane and extraction evaporated to obtain Biofat. The residue biofat charred shell after the extract to produce Biochar and Biosmoke. Proximate analysis performed on fresh shells, biofat, biochar and biosmoke. The result biofat yield increased three-fold when the size of the shell is reduced to 2 mm (17.81 g/100g BK), while biochar and biosmoke increased two-fold when the size of the shell is enlarged 1 cm (30.82 g/100g BK and 5:13 g/100g BK). Biofat containing coarse fat and high total phenol (94.43 g/100g biofat, 46 mg/100g biofat) and total phenol containing biosmoke quite high (7.2 mg/100g biosmoke) on a large particle size. The results of GC-MS analysis showed biofat and biosmoke acidic anacardic high (74%) and biochar contains minerals especially high ash content (6:56%), Ca (0.69%), and P (12:23%) 2-fold increase in the particle size of the shell smaller than the large. Mineral Fe (695 mg/kg) more contained shells of large particles, whereas the characteristic biosmoke have a high acid content (pH 3). Cashew nut shell bioindustry products have specific physical and chemical characteristics to be used in various fields including livestock, agriculture or food.